Annual report - Leweko Resources Berhad (Ipoh : Leweko Resources Berhad, 2006)
Annual report for the year 2005 for Leweko Resources Berhad, a company that managed logs and timber products, plantation, which is oil plam and also timber harvesting and logging contracting
System requirements : Windows 98 or later, Pentium II or higher processor recommended, 32 MB RAM or more, Power Macintoch and above, 32 MB RAM or more
Keywords: Forest products industry; Logging -- Economic aspects; Timber -- Economic aspects; Palm oil